Sprint runners have longer achilles tendon moment arm than distance runners - Kovács, B.; Hegyi, A.; Yaodong, G.; Kóbor, I.; Gyebnár, G.; Tihanyi, J.; Péter, A. (Journal of Biomechanics, 2025)
The length of the Achilles tendon moment arm may affect muscle shortening velocity, ankle moment, and running economy in running. Regarding the direction of these effects, experimental studies are controversial. These typically use simplified 2-D methods to define the length of the moment arm, and data on high-level athletes are scarce. The purpose of this study was to use a 3-D approach to estimate the length of the Achilles tendon moment arm and examine its association with sprint and endurance running performance in high-level competitive runners. Twenty-nine healthy adult competitive runners were recruited, including fifteen distance runners (IAAF score = 953 ± 116, mean ± standard deviation) and fourteen sprint runners (IAAF score = 993 ± 113). The length of the Achilles tendon moment arm was estimated from T1 weighted MRI scans taken at a 90° ankle angle. The sprint runners had longer Achilles tendon moment arms compared to the distance runners when considering absolute lengths (51.8 ± 2.1 mm vs. 48.7 ± 3.8 mm, p = 0.017, Cohen`s d = -0.94), as well as after normalizing to body height (p = 0.004, d = -1.14). However, we did not find any correlation between the absolute or normalized Achilles tendon moment arm length and personal best running performance in either group. However, longer moment arm may be due to the relatively larger plantar flexor muscle size which can probably offset the detrimental effects of a longer moment arm. On the other hand, distance runners may benefit from a relatively shorter moment arm due to lower forces and increased need for fatigue-resistance. We found no evidence that plantar flexor moment arm is detrimental to running performance in either group, therefore, practitioners should not be concerned about the effects of increasing muscle size on the increase in Achilles tendon moment arm.